2022
DOI: 10.1097/olq.0000000000001636
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Motives for Complying With “Sexual Distancing” Among Men Who Have Sex With Men During the First COVID-19 Pandemic Lockdown in Amsterdam: A Qualitative Study

Abstract: A qualitative study in a sexual health setting found that sexual distancing information to prevent severe acute respiratory syndrome coronavirus 2 transmission needs to be provided in a more explicit, accessible, understandable, and inclusive manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…These findings underscore the importance of focusing campaigns not only on social distancing, but also explicitly on sexual distancing, for a more effective prevention of disease transmission. This is supported by our previous qualitative study where we found that some participants were not aware that sexual distancing is part of social distancing 3 . We also found that the number of participants that were solely socially or sexually compliant was relatively stable throughout the four periods.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These findings underscore the importance of focusing campaigns not only on social distancing, but also explicitly on sexual distancing, for a more effective prevention of disease transmission. This is supported by our previous qualitative study where we found that some participants were not aware that sexual distancing is part of social distancing 3 . We also found that the number of participants that were solely socially or sexually compliant was relatively stable throughout the four periods.…”
Section: Discussionsupporting
confidence: 86%
“…Data were collected between 25 November 2021 and 3 March 2022. The questionnaire was developed using the findings from our previous qualitative study on sexual distancing3; items were translated into quantifiable items on a 5-point Likert scales. The questionnaire was available in Dutch and English and piloted by three people who were unrelated to the Center for Sexual Health in Amsterdam and the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceived risk of SARS-CoV-2 infection and public health measures were found to be associated with a change in sexual behaviour [10,11]. A recent study from Bilsen et al [9] found that distancing measures during lockdown led to a temporary decrease in casual sex partners and a relatively low STI positivity rate among clients of the CSH in Amsterdam [9].…”
Section: Introductionmentioning
confidence: 99%
“…The perceived risk of SARS-CoV-2 infection and public health measures were found to be associated with a change in sexual behaviour [10, 11]. A recent study from Bilsen et al .…”
Section: Introductionmentioning
confidence: 99%